Transformation of imine cages into hydrocarbon cages - Schick, Tobias Hans Günter; Lauer, Jochen; Rominger, Frank; Mastalerz, Michael (Angewandte Chemie. International edition, 2019)
Abstract In contrast to organic cages which are formed by exploiting dynamic covalent chemistry, such as boronic ester cages, imine cages, or disulfide cages, those with a fully carbonaceous backbone are rarer. With the exception of alkyne metathesis based approaches, the vast majority of hydrocarbon cages need to be synthesized by kinetically controlled bond formation. This strategy implies a multiple step synthesis and no correction mechanism in the final macrocyclization step, both of which are responsible for low overall yields. Whereas for smaller cages the intrinsic drawbacks are not always obvious, larger cages are seldom synthesized in yields beyond a few tenths of a percent. Presented herein is a three-step method to convert imine cages into hydrocarbon cages. The method has been successfully applied to even larger structures such as derivatives of C72H72?, an unknown cage suggested by Fritz Vögtle more than 20 years ago.